THE CHARACTERISTICS OF COPYING STRATEGIES AND LOCUS OF CONTROL OF FIRST-YEAR STUDENTS IN PSYCHOLOGY - Novikova, Zhanna (PSYCHOLOGICAL JOURNAL, 2020)
The article considers the modern approaches examining coping strategies and the locus of control. The main structural components of coping strategies are identified, namely: cognitive, emotional and behavioural. The most often used coping strategies are: social support, professional help, emotional reactions, ignoring or avoidance of problems. The basic functions of coping strategies are considered and defined: problem-oriented and emotionally-oriented. The main concepts concerning copings are defined and analyzed: coping-behaviour, coping-resource, and coping-strategy. An individual’s coping resources are: adequate self-esteem, achievement motivation, low anxiety, as well as flexible reaction to changes, self-confidence, the ability to solve life problems, constructive defence of own opinions, resistance to pressure from others, established and maintained social contacts. The role of such communicative resources for coping as empathy and affiliation is also analyzed.The main approaches to the locus of control are analyzed and its main types are distinguished: internal, external and ambernal loci of control. The exsicting correlations between coping strategies and loci of control were proven.It is important to form active, constructive coping strategies and internal locus of control at fresh students during their adaptation to university. The article presents the empirical study examining students’ coping strategies and locus of control. We have determined that first-year students actively use such coping strategies as forecasting, decision-making, correction, self-control. Such strategies as quality assessment, goal setting, planning are used less often. The first-year students are more likely to use internal locus control in interpersonal relationships, at attitudes toward health and achievement. Students show internal as well as external loci of control in the field of failures and family relations.